The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/jvim.16804
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐two cats with effusive or non‐effusive feline infectious peritonitis treated with a combination of remdesivir and GS‐441524

Abstract: BackgroundGS‐441524 has been successfully used to treat feline infectious peritonitis (FIP) in cats. However, the use of its prodrug, remdesivir, in combination with a PO GS‐441524 containing product for the treatment of FIP has not yet been described.ObjectivesDescribe treatment protocols, response to treatment and outcomes in cats with FIP treated with a combination of PO GS‐441524 and injectable remdesivir.AnimalsThirty‐two client‐owned cats diagnosed with effusive or non‐effusive FIP including those with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(62 citation statements)
references
References 20 publications
5
42
0
1
Order By: Relevance
“…The legality of the drugs has facilitated access to data relating to direct veterinary input into the care of these cats. In agreement with previous studies 10,11,22,28 33,40,42 reporting the use of varied (usually unregulated or illegal) nucleoside analogue preparations, in the present study, all three treatment protocols (ie, remdesivir alone, remdesivir then GS-441524 and GS-441524 alone) were highly effective in treating this previously fatal disease. An impressive 88.6% of cats were alive at the end of the initial treatment period, and 84.4% at the longest follow-up time point after completion of the initial treatment period (ie, at a median [range] of 180 [0–730] days).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The legality of the drugs has facilitated access to data relating to direct veterinary input into the care of these cats. In agreement with previous studies 10,11,22,28 33,40,42 reporting the use of varied (usually unregulated or illegal) nucleoside analogue preparations, in the present study, all three treatment protocols (ie, remdesivir alone, remdesivir then GS-441524 and GS-441524 alone) were highly effective in treating this previously fatal disease. An impressive 88.6% of cats were alive at the end of the initial treatment period, and 84.4% at the longest follow-up time point after completion of the initial treatment period (ie, at a median [range] of 180 [0–730] days).…”
Section: Discussionsupporting
confidence: 92%
“…One study limitation and interesting discussion point is that only 9.5% of cats in the study met the stringent diagnostic criteria that confirms a diagnosis of FIP, with only another one-third of cats (33.2%) having FCoV RNA detected in samples, leading to a diagnosis of FIP being ‘very likely’, the remainder being highly suspicious. This lack of definitive diagnosis in many cats is not dissimilar to other studies on the outcome of cats treated for FIP 10,11,22,29 33,40 because, increasingly, financial resources for treatment are being prioritised over those to confirm the diagnosis, and the ability to perform further diagnostic testing in a case can be problematic due to access to testing or the condition of the cat. A positive response to treatment in suspected cases of FIP is sometimes used as strong diagnostic support for FIP.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2/5 Katzen wurden aufgrund aufgetretener neurologischer Symptome euthanasiert. Zum Zeitpunkt der Veröffentlichung hatten 10 Katzen den 84-tägige Behandlungszyklus mit Remdesivir und GS-441524 erfolgreich abgeschlossen und befanden sich in Remission 77 .…”
Section: Antivirale Chemotherapieunclassified
“…Historically considered a fatal disease, recent research has revealed efficacy of new antivirals in FIP treatment, making an early diagnosis even more critical. [7][8][9][10][11][12] Immunohistochemistry (IHC) for the FCoV antigen in affected tissues is considered the gold standard for the diagnosis of FIP. 7 In the absence of a definitive diagnosis, background, clinical signs, routine laboratory tests and molecular analyses can be combined to establish a high index of suspicion of FIP.…”
Section: Introductionmentioning
confidence: 99%